A microphone in a chandelier: How a secret recording sparks mnemonic imagination and affect. (April 2023) - Pogačar, Martin
In this study, I examine a recording of an old Slovenian choral song made in 1941 during the Fascist occupation. Recorded music, I argue, has the capacity to condense the past and to potentiate the affective mnemonic imagination of the past regardless of its mediated form. To make this argument, I investigate the recording as a temporal object that drives affective mnemohistories; modulates individual and collective experiences, expectations and interpretations; and induces mnemonic imagination. I discuss the song's pre-recorded historical background and the technical history of the recording, and the song's affective force in live performances as compared to the mediated experience in YouTube. The investigation of the song as a temporal object that engenders variegated, multilayered engagements with the past contributes to the debates on the study of music and memory, and the history of media technologies in the context of post-socialist memory.